Bubuk Limbah Botol Kaca sebagai Pengganti Parsial Agregat Halus dalam Campuran Beton - Nura Diana, Anita Intan; Fansuri, Subaidillah; Zainah, Nor (Universitas Dr. Soetomo, 2021)
Glass bottles waste are generated from industrial and household activities that can’t be decomposed, if the amount is too much it will damage for the environment. In this study, glass waste will be reused as a filler in concrete especially fine aggregate, because glass bottles waste has weather resistance. The data was analyzed by using regression and classical assumption test with SPSS programme with the help of SPSS 20 for windows software. The variables used in this study were the independent variable (glass bottle waste) and the dependent variable (tensile strength). Based on the results of the analysis, it is obtained that the maximum tensile strength is at the variation of 0% and 12.5%, where at the 0% variation, the tensile strength is obtained at 44 Kg/cm, while at the 12.5% variation, the tensile strength is obtained at 40 Kg/cm. This can be seen in the results of the simple linear regression analysis using the SPSS 20 for windows program which shows that the effect of adding glass waste has a significant effect on tensile strength.